The ACA Medicaid Expansions and Opioid Mortality: Is There a Link?. (December 2021) - Abouk, Rahi; Helmchen, Lorens; Moghtaderi, Ali; Pines, Jesse
The Medicaid expansions made addiction treatment more accessible but they also made it less costly to obtain the prescription opioids that can trigger an addiction. We investigated the association between the Medicaid expansions and drug-related deaths. We add to the literature by explicitly accounting for the properties of illicit drug markets and by conducting a simulation-based power analysis to assess whether a plausible change in drug-related mortality could be detected with our data. We identify three main challenges in isolating the effect of the Medicaid expansions on drug-related mortality that cannot be sufficiently addressed with current data: (a) nonparallel preexpansion trends in drug-related mortality, (b) the contemporaneous surge in the supply of illicitly manufactured fentanyl, and (c) lack of statistical power. We argue that more comprehensive data are needed to answer this question.